BLUEPRINTS in black and white: The built environment professions in South Africa - an outline history by John Bizzell - Kotze, Paul (Acta Structilia, 2009)
BLUEPRINTS in black and white, is intended as a brief history of the Bbuilt environment professions in South Africa. Its aim is to assist in the understanding of the role of these professions in the South African society. The content of the book is broadly based on the assumption that South African built environment professionals have always reflected the dominant societal values and attitudes of the day.